(7x-3)(7x-3)=0

Simple and best practice solution for (7x-3)(7x-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x-3)(7x-3)=0 equation:


Simplifying
(7x + -3)(7x + -3) = 0

Reorder the terms:
(-3 + 7x)(7x + -3) = 0

Reorder the terms:
(-3 + 7x)(-3 + 7x) = 0

Multiply (-3 + 7x) * (-3 + 7x)
(-3(-3 + 7x) + 7x * (-3 + 7x)) = 0
((-3 * -3 + 7x * -3) + 7x * (-3 + 7x)) = 0
((9 + -21x) + 7x * (-3 + 7x)) = 0
(9 + -21x + (-3 * 7x + 7x * 7x)) = 0
(9 + -21x + (-21x + 49x2)) = 0

Combine like terms: -21x + -21x = -42x
(9 + -42x + 49x2) = 0

Solving
9 + -42x + 49x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(3 + -7x)(3 + -7x) = 0

Subproblem 1

Set the factor '(3 + -7x)' equal to zero and attempt to solve: Simplifying 3 + -7x = 0 Solving 3 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -7x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -7x = 0 + -3 -7x = 0 + -3 Combine like terms: 0 + -3 = -3 -7x = -3 Divide each side by '-7'. x = 0.4285714286 Simplifying x = 0.4285714286

Subproblem 2

Set the factor '(3 + -7x)' equal to zero and attempt to solve: Simplifying 3 + -7x = 0 Solving 3 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -7x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -7x = 0 + -3 -7x = 0 + -3 Combine like terms: 0 + -3 = -3 -7x = -3 Divide each side by '-7'. x = 0.4285714286 Simplifying x = 0.4285714286

Solution

x = {0.4285714286, 0.4285714286}

See similar equations:

| -9x+60x=6x | | (-8x^7y)(x^3y^7)=0 | | -9x+60=6x | | (1/7)(1/7)(1/7) | | (2k^3)^4/4k^5 | | 6x-23=14x+49 | | (8x+7)(x^2-4x+1)=0 | | 20x+16=94 | | 4x^2+24x+19=0 | | 4x^2+24+19=0 | | 8x+13=109 | | 7/12*y-1/4=2y-5/3 | | 2+8x=24 | | (5x-8)(2x+9)=0 | | (8x^2-3x^3)-(6x^2-8x^3)=0 | | 3x^2+20x+7=-4x^2-4x+24 | | 4x^2+9y^2+32x=-28 | | (2x+y+1)dy+(4x+2y-1)dx=0 | | 42/-21 | | (-32x^-5)^-3/5 | | 8cosX+21sinX=18 | | (4x^2+9x)+(3x^2+5x+18)-(7x^2-12)= | | 3x^2-ix-4=0 | | 4x-2(5-2x)=6 | | -4(-5w+7)-9w=7(w-1)-3 | | 80x+60(420-x)=31100 | | 5(w-5)-8w=-1 | | 10x+x^2+25=0 | | 22x^2+40x=80 | | -4x+(1+2x)=-1 | | n/80=5/100 | | log^36x=5/2 |

Equations solver categories